Fractional tunnelling resonance in plasmonic media - Kang, Ji-Hun; -Han Park, Q. (Scientific reports, 2013)
Metals can transmit light by tunnelling when they possess skin-depth thickness. Tunnelling can be resonantly enhanced if resonators are added to each side of a metal film, such as additional dielectric layers or periodic structures on a metal surface. Here we show that, even with no additional resonators, tunnelling resonance can arise if the metal film is confined and fractionally thin. In a slit waveguide filled with a negative permittivity metallic slab of thickness L , resonance is shown to arise at fractional thicknesses ( L = Const./ m ; m = 1,2,3,…) by the excitation of ‘vortex plasmons'. We experimentally demonstrate fractional tunnelling resonance and vortex plasmons using microwave and negative permittivity metamaterials. The measured spectral peaks of the fractional tunnelling resonance and modes of the vortex plasmons agree with theoretical predictions. Fractional tunnelling resonance and vortex plasmons open new perspectives in resonance physics and promise potential applications in nanotechnology.